Social Media Usage by Higher Education Academics - Zulvia Trinova; Dina Destari; Pandu Adi Cakranegara; Erna Adita Kusumawati; Arjulayana Arjulayana (STAI Hubbulwathan Duri, 2022)
The use of social media among academics as a means of communication and information. This research is qualitative research with the aim of getting an overview of the use of social media among universities. In general, the use of social media as a medium of learning has been applied in almost all universities today. The method in this study using online observation and scoping review was used to collect information, and literature was collected from several databases such as the Proquest and Science Direct website, Google Scholar, and Mendeley. Furthermore, the material is divided into several sections so that relevant literature can be collected and used in conjunction with teaching and learning activities in higher education institutions. The results of this study indicate that learning ideas can be learned and implemented through the use of social media. It has the potential to increase teaching and learning effectiveness, as well as to promote group learning and collaborative learning opportunities. Learning tools such as e-books and online films can be accessed through social media platforms. Social media can help in developing innovative ideas in academics and education. The conclusion of this study is that the use of social media is very effective as a learning medium for universities